THE EXTENSION OF POSSIBILITIES OF THE SOFTWARE AT USAGE OF KNOWLEDGE BASES, BASED ON OWL 2.0 - Плиско, Дмитрий Анатольевич; Шевченко, Александр Юрьевич (Eastern-European Journal of Enterprise Technologies, 2010)
In this article the advantages of the ontology-based knowledge bases using were examined. The differences from previous standards, that most fully demonstrate distinctions of OWL 2.0 were examined.